Color Plays Tricks - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet describes how colors may be emotional or physical stimuli. The booklet lists emotions associated with several colors then encourages readers to assess the colors of their home and paint their walls to maximize cheer. Includes small stylized illustrations throughout, and decorated covers. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Paint materials; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Interior decoration; Symbolism of colors; Color--Social aspects